The Determinant of Minimum Capital Policy, Motivation, Risk, Benefits, and Knowledge on Investment Decisions of MSMEs in Central Lombok - Baiq Dewi Sulistiani; Tri Hanani (International Economic Conference of Business and Accounting, 2025)
Investment decisions have a significant impact on the steps that potential investors will take, particularly in relation to the research object, namely MSMEs. This study aims to determine the influence of minimum capital policies, motivation, risk, benefits, and knowledge on investment decisions. Primary data was collected through online questionnaires distributed to 121 MSMEs in Central Lombok and analyzed using multiple linear regression (PLS-SEM). The results show that motivation, risk, and benefits have a positive influence on investment decisions among MSMEs in Central Lombok. These findings are crucial for understanding the factors related to investment decisions in Indonesia. This research provides significant insights for policymakers in making decisions about investor behavior and identifying the factors influencing investment decisions of MSMEs in Central Lombok, and it is hoped that this research can make a significant contribution to the development of policies that support the growth of MSMEs in the region.